The human GIMAP5 gene has a common polyadenylation polymorphism increasing risk to systemic lupus erythematosus. Issue 5 (12th January 2007) - Hellquist, Anna; Zucchelli, Marco; Kivinen, Katja; Saarialho-Kere, Ulpu; Koskenmies, Sari; Widen, Elisabeth; Julkunen, Heikki; Wong, Andrew; Karjalainen-Lindsberg, Marja-Liisa; Skoog, Tiina; Vendelin, Johanna; Cunninghame-Graham, Deborah S; et al.
Abstract : Background: Several members of the GIMAP gene family have been suggested as being involved in different aspects of the immune system in different species. Recently, a mutation in the GIMAP5 gene was shown to cause lymphopenia in a rat model of autoimmune insulin-dependent diabetes. Thus it was hypothesised that genetic variation in GIMAP5 may be involved in susceptibility to other autoimmune disorders where lymphopenia is a key feature, such as systemic lupus erythematosus (SLE). Material and methods: To investigate this, seven single nucleotide polymorphisms in GIMAP5 were analysed in five independent sets of family-based SLE collections, containing more than 2000 samples. Result: A significant increase in SLE risk associated with the most common GIMAP5 haplotype was found (OR 1.26, 95% CI 1.02 to 1.54, p = 0.0033). In families with probands diagnosed with trombocytopenia, the risk was increased (OR 2.11, 95% CI 1.09 to 4.09, p = 0.0153). The risk haplotype bears a polymorphic polyadenylation signal which alters the 3′ part of GIMAP5 mRNA by producing an inefficient polyadenylation signal. This results in higher proportion of non-terminated mRNA for homozygous individuals (p<0.005), a mechanism shown to be causal in thalassaemias. To further assess the functional effect of the polymorphic polyadenylation signal in the risk haplotype, monocytes were treated with several cytokines affecting apoptosis. All the apoptotic cytokines induced GIMAP5 expression in two monocyte cell lines (1.5–6 times, p<0.0001 for all tests). Conclusion: Taken together, the data suggest the role of GIMAP5 in the pathogenesis of SLE.